Overhauling the WTO: Opportunity at Doha and beyond - AUDLEY, John (Institutional Knowledge at Singapore Management University, 2001)
The world's trade ministers, who will meet at a WTOministerial in November 2001 in Doha, Qatar, are wrong to think that only a newround of negotiations will save the much-maligned international trade system.Carnegie senior associates John Audley and Ann M. Florini argue that theyshould, instead, simultaneously tackle internal and external reform of the WTOto make it a truly equitable institution. Internally, industrial countries muststart treating developing countries as equal partners in making the rules thatgovern global trade, and where necessary provide technical assistance to makethat equality possible. Externally, to satisfy legitimate public demands,members should improve the transparency of WTO proceedings and permit publicparticipation in keeping with international norms. These changes, however, willoccur only when national leaders link internal and external reform objectives—astep that will require leadership from key countries as well as the WTOSecretariat.